Complete mitochondrial genome of the brown alga Sargassum vachellianum (Sargassaceae, Phaeophyceae). (3rd July 2016) - Bi, Yanhui; Zhou, Zhigang
Abstract: Sargassum vachellianum C. Agardh is endemic to China. It inhabits in rocky intertidal zones and plays an important role in maintaining the structure and function of littoral ecosystems. In this study, we present the complete mitochondrial genome of S. vachellianum . The circular S. vachellianum mitogenome is 34, 877 bp in size and contains the same set of 65 genes as the reported Sargassum mtDNAs. The overall AT content of the genome is 63.79%, and the inter-genic spacers constitute only 4.67%. The genome organization including the gene order, overlapping regions between genes, and the total length of inter-genic spacers is conserved among the known Sargassum mitogenomes. High divergence is in inter-genic spacer regions. Phylogenetic analyses indicated that S. vachellianum combined tightly with Sargassum species with strong support values (NJ/ML, 100%).